(untitled) (Journal of Multidisciplinary Research Advancements, 2023)
Occupational health is a vital aspect of public health that aims to ensure the well-being of workers in various occupations. It encompasses multiple academic fields, such as occupational medicine, nursing, ergonomics, psychology, hygiene, and safety. Despite global efforts to improve occupational health, access to occupational health and safety (OHS) services remains low in many countries, including South Africa, Zimbabwe, Zambia, Botswana, China, and Nepal. This review paper was conducted through an extensive literature review. Databases such as Science Direct, Springer, NepJol, PubMed, and Google Scholar were searched to access a wide range of scholarly articles, research papers, and reports. The findings reveal that occupational workers face various hazards, including exposure to infectious diseases, radiation, hazardous chemicals, noise, and psychosocial risks. In Nepal, workers in industries such as agriculture, construction, and brick manufacturing are particularly vulnerable to these hazards. Lack of proper safety measures, inadequate access to clean drinking water and sanitation, child labor, and physical strain contribute to the high incidence of work-related diseases and injuries among workers. The study also highlights the policies and initiatives undertaken by the government of Nepal to improve occupational health and safety, including the Labor Act of 1992, the Occupational Safety and Health Project, and the Nepal National Building Code. The study emphasizes the urgent need to improve occupational health and safety conditions in Nepal. It highlights the importance of implementing preventive measures, raising awareness, providing training and education, and establishing standards to protect the health and well-being of workers.